2017
DOI: 10.1016/j.scitotenv.2016.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal di-2-ethylhexyl phthalate exposure and cord blood adipokine levels and birth size: The Hokkaido study on environment and children's health

Abstract: Di-2-ethylhexyl phthalate (DEHP) is one of the most widely used phthalates. Metabolites of DEHP are detectable in majority of the population. Findings on adverse health outcomes, particularly birth weight in association with prenatal exposure to DEHP remain equivocal. Besides, there is insufficient evidence to address influence on metabolic function from epidemiological studies. Thus, our objective was to investigate cord blood adipokine levels and birth size in association with prenatal DEHP exposure in prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…The results are shown in Table 7 . We observed that PCDD/PCDFs and PFASs were associated with decreased birth weight [ 33 , 34 ]; however, DEHP, PCBs, and total Hg were not associated with birth weight [ 35 , 36 ]. Our investigation not only was on conventional birth weight but also included cord adipokines considered to be biomarkers of metabolic function [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are shown in Table 7 . We observed that PCDD/PCDFs and PFASs were associated with decreased birth weight [ 33 , 34 ]; however, DEHP, PCBs, and total Hg were not associated with birth weight [ 35 , 36 ]. Our investigation not only was on conventional birth weight but also included cord adipokines considered to be biomarkers of metabolic function [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“… [ 37 ] DEHP Ponderal index 167 Significant decrease (per log10 unit: β = −1.28, 95% CI − 2.43 to − 0.13). [ 35 ] Cord adipokines 167 Significant decrease in leptin among girls (per log10 unit: β = −0.31, 95% CI − 0.52 to − 0.10). Significant increase in adiponectin among boys (per log10 unit: β = 4.63, 95% CI 0.77 to 8.49).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group has reported that maternal MEHP levels were MINATOYA 20 associated with alternation of adiponectin and leptin levels in cord blood in sex-specific manner (Minatoya et al 2017). Cord blood adipokine levels can be investigated in association with these environmental chemical exposures in our future work.…”
Section: Minatoya 19mentioning
confidence: 92%
“…spontaneous abortion and increased blood pressure) (Jukic et al, 2016;Mu et al, 2015;Toft et al, 2012;Werner et al, 2015), adverse birth outcomes (e.g. preterm birth, low birth weight and decreased birth length) Huang et al, 2009;Latini et al, 2003;Meeker et al, 2009;Minatoya et al, 2017;Philippat et al, 2012;Wolff et al, 2008;Zhang et al, 2009), and impaired children growth (Valvi et al, 2015) and neurodevelopment (e.g. lower IQ, problems with attention, hyperactivity and poorer social communication) (Miodovnik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%